Information Needs to Influence the Quality of Development Messages and News in the Digital Media Era - Iman Indrati; Sumardjo Sumardjo; Dwi Retno Hapsari; Anna Fatchiya (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The presence of development journalists is needed to criticize, study, evaluate, and report on the relevance of development projects. The press, as the fourth pillar of democracy, has a very crucial role in conveying criticism. The research aims to analyze the influence of society's information needs (X1), politics (X2), and government (X3) on the quality of development messages (Y1) and news (Y2). The research methodology uses a mixed-methods approach with a sequential explanation strategy. TheÂ  research population coversÂ  television news viewers and observers. The research sample consisted of 110 respondents who were viewers and observers of news broadcasts in mainstream media. The research results show: (1) there is a significant influence between the information need variable based on the community perspective (X1) on the quality of development messages (Y1); (2) there is no significant influence between the variable information needs based on the perspective of the business world (X2), politics (X3), and government (X4) on news quality (Y2), but there is an influence of public information needs (X1) on news quality (Y2). Based on information from press representative institutions, there was a decline in quality caused by: (1) complaints of violations from the Indonesian Broadcasting Institution; (2) less attractive news packaging; (4) social media competition; (5) in-depth news analysis; (6) intervention from stakeholders; (7) lack of cross-sectoral support; and (8) the small compensation received by journalists. In conclusion, information needs based on society's perspective do not influence the quality of development messages but do influence the quality of news.